Oasis of wisdom : the worlds of the Desert Fathers and Mothers - Keller, David G. R., 1937- (Collegeville, Minn. : Liturgical Press, 2005)
"Introduces readers to the wisdom of the desert elders in the context of their daily lives, presenting their background (historical, cultural, and religious) and describing the environment of solitude, ascetic disciplines, labor, and interactions with other people that was the source of their wisdom"--Provided by publisher.
Includes bibliographical references (p. 166-168) and index.
Keywords: Spiritual life -- Christianity -- History of doctrines -- Early church, ca. 30-600.; Desert Fathers; Monastic and religious life of women -- Egypt -- History -- Early church, ca. 30-600.